Penggambaran Peta Situasi Menggunakan Feature Line & Grading Civil 3D - Parmono Parmono (Universitas Pendidikan Indonesia, 2021)
Mapping is a series of processes from surveys, data processing to plotting depictions. For the description of locations with many buildings, then flat surface plots as building footprints must be described with the same height, no contour lines hitting the building. The drawing begins with plotting point coordinates, describing a flat polygon on a building site plot with surface lines and grading and then generating a surface from civil 3d. The results illustrate that there are no contour lines that intersect the building, in contrast to the generated surface which is carried out without drawing a flat plot of land